2013
DOI: 10.1021/ol401317m
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Sonogashira-Type Cross-Coupling of Alkynes with Fluoroarenes

Abstract: A novel, inexpensive, and efficient palladium-, copper-, ligand-, and amine-free Sonogashira-type cross-coupling reaction of terminal alkynes with unreactive aryl fluorides in the presence of sodium, sodium methoxide, and calcium hydroxide under the assistance of a Grignard reagent was developed. A plausible mechanism was also suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…MS (EI): m/z (%) = 242 (71) [M] + . [35] 7.53-7.45 (m, 4 H), 7.37-7.30 (m, 3 H), 6.87 (dt, J = 8.9, 2.1 Hz, 2 H), 3.83 (s, 3 H) ppm. 13 C NMR (75 MHz, CDCl 3 ): δ = 159.…”
Section: Methodsmentioning
confidence: 99%
“…MS (EI): m/z (%) = 242 (71) [M] + . [35] 7.53-7.45 (m, 4 H), 7.37-7.30 (m, 3 H), 6.87 (dt, J = 8.9, 2.1 Hz, 2 H), 3.83 (s, 3 H) ppm. 13 C NMR (75 MHz, CDCl 3 ): δ = 159.…”
Section: Methodsmentioning
confidence: 99%
“…[3,4] Alkynylated fluoroarenes, also obtained through S N Ar reactions, are potentially applicable in electronic materials and can be used for further transformations based on their alkynyl moieties. [5][6][7][8] For example, Zhao, Zhang, and co-workersr eported the alkynylation of polyfluoroarenes with terminal alkynesu sing as toichiometric amount of nBuLi (Figure 1, i). [5] Cao andc o-workersa lso noted that the reaction using terminal alkynesi sm ediated by Na and nBuMgCl throughaS RN 1m echanism involving one-electron transfer,i nw hich poorly reactive mono-or difluoroarenes are also transformedb yf urther addingN aOMea nd Ca(OH) 2 (Figure 1, ii).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Cao andc o-workersa lso noted that the reaction using terminal alkynesi sm ediated by Na and nBuMgCl throughaS RN 1m echanism involving one-electron transfer,i nw hich poorly reactive mono-or difluoroarenes are also transformedb yf urther addingN aOMea nd Ca(OH) 2 (Figure 1, ii). [6] Alternatively,W atson and co-workers showed that alkynylated products of hexafluoroarene are formed by using aryl alkynyls ilanes as nucleophilesi nt he presence of a catalytic amount of tetrabutyla mmonium fluoride( TBAF) (Figure 1, iii). [7] They also appliedt he protocol to the preparation of poly(phenylene ethynylene)s bearing alternating arylpolyfluoroaryl units.S anji and co-workers reported that monosubstituted polyfluoroarenes undergo substitution reactions with alkynyl silanes in the presence of CsF and 18-crown-6 (Figure 1, iv).…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, They repported the first example of transition-metal-free Suzuki-type coupling reactions. [13] in 2013, Cao , s [14] group described the examples of transition-metal-free Sonogashiratype cross-couplings. Besides, Eycken's group [15] demonstrated the transition-metal-free cross-coupling of aryl halides with phenylacetylene in water at 175°C (Scheme 1, Eq 2).…”
mentioning
confidence: 99%
“…[c] 3-iodoquinoline was used as the substrate, [d] 3-iodopyridine was used as the substrate. 14,[16][17][18][19]. In addition, the Sonogashira cross-coupling of 3iodoquinoline and 2-iodopyridine with phenylacetylene equally proceeded smoothly to afford the desired products in 89 % and 91 % yields, respectively ( .…”
mentioning
confidence: 99%